The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.5603/fm.a2019.0111
|View full text |Cite
|
Sign up to set email alerts
|

An odontometric study of tooth dimension in diastematic dentition

Abstract: Background:One of the cause of the maxillary midline diastema (MMD) may be discrepancy between teeth and maxilla dimension. That can relate to two situations: when teeth have correct size but maxilla is too large or maxilla bone is in the proper size but teeth have reduced dimensions (microdontia). The present study has been conducted to investigate the differences in the linear dimensions of upper central and lateral incisors and canines in diastematic dentition and to compare them with the control group with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These results are in accordance with those found in the Sękowska and Chałas study that revealed statistically significant differences in the length of central incisors and canines on both sides, and that all measurements of teeth proportions were lower in the diastema group. 7 Several treatment modalities can be used for diastema closure. These include orthodontic treatment or restorative dentistry using such materials as ceramics or composite-based resins.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with those found in the Sękowska and Chałas study that revealed statistically significant differences in the length of central incisors and canines on both sides, and that all measurements of teeth proportions were lower in the diastema group. 7 Several treatment modalities can be used for diastema closure. These include orthodontic treatment or restorative dentistry using such materials as ceramics or composite-based resins.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with the later digital models, the characteristics of long-term storage reliability, space occupation, and fragility of the plaster model have become obvious disadvantages. Currently, dental clinics prefer to use digital models as an alternative (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%